Extent of Adoption of Available Components in the IFS Units of Kerala - Vani Chandran,; Ritu Chakravarty, (Indian Journal of Extension Education, 2022)
Integrated Farming Systems (IFS) have shown to be an important way to improve the intake of safe and micro nutrient rich foods, particularly for households of Kerala. The productivity and profitability from a unit directly depends on the components adopted. Keeping this in mind, the present study was carried out with an objective to measure the extent of adoption of various components among the existing integrated farming system units of Kerala during 2021-22. Three districts Kollam, Thrissur and Kannur were selected randomly. From each district four panchayat were randomly selected and fifteen IFS units were selected randomly from each identified panchayat, thus making the total sample size 180 integrated farming system units. To measure the extent of adoption of available components in the IFS units, a composite index was developed. The result revealed that majority of the IFS farmers exhibited low level adoption of available components in their units and among the components, dairy and crop component had the highest adoption rate.